Breast compression and experienced pain during mammography by use of three different compression paddles. Issue 115 (June 2019) - Moshina, Nataliia; Sebuødegård, Sofie; Evensen, Kate Torild; Hantho, Caroline; Iden, Kari Alette; Hofvind, Solveig
Highlights: Mean pain scores ranged between 2.4 and 2.6 on a numeric rating scale. Mean reported pain score was the highest for the fixed paddle. Optimized compression pressure was associated with a higher mean glandular dose. Shoulder/neck pain prior screening was associated with higher pain scores. Abstract: Objectives: We aimed to compare pain experienced during screening mammography, using three different compression paddles: a fixed paddle standardizing pressure (study paddle), a flexible, and a fixed paddle. Material and methods: Using a numeric rating scale (NRS), ranged 0–10, we collected information on pain experienced during mammography from a questionnaire completed by 4, 675 women screened in Stavanger, May-November 2017, as a part of BreastScreen Norway. The questionnaire also provided information on factors possibly associated with pain. Data on compression force, pressure and breast characteristics were extracted from the DICOM-header, and a breast density software. T-tests were used to compare mean values of the parameters between the types of compression paddles. Linear regression was used to determine the association of a score of ≥7 versus <7 on NRS for experienced pain by compression paddle, adjusting for pressure, breast characteristics and associated factors. Results: The mean of experienced pain did not differ for the study and flexible paddle (2.5 on NRS), and was lower for the study paddle compared to the fixed paddle (2.4 versus 2.6 on NRS, p < 0.05). Pain in shoulder(s) and/or neck prior to mammography was associated with 33% (RR 1.33, 95%CI 1.07–1.65) higher risk of a score of ≥7 versus <7 for experienced pain. Conclusion: The majority of women reported low scores of experienced pain during mammography, independent of compression paddle used. Further research on image quality is needed to fully understand which paddles should be preferred in a screening setting.